Simulation model of space optimization in containers arranging and sequencing for logistics - Kimpan, Warangkhana; Tantawarak, Nake (My University, 2013)
This paper proposes the application using 3D Bin Packing to optimize the container space for logistics system. The aim is to reduce logistics costs, arrangement time and delivery time. The application can arrange different sizes of cubical boxes into the container bin of trucks, vans, or wagons considering their distributing sequence by using Best-Fit Decreasing algorithm to optimize the space. It also can be used to reduce the cost of product delivering because the container will be divided into many partitions and arranged by using delivery sequence. The different types of boxes and vehicles can be freely adjusted and arranged. The arranged boxes can be viewed in order to check their position. The experimental results of the application are shown in 3D with freely movement view.
Keywords: 3D Bin Packing; Best-Fit Decreasing Algorithm; Container Arrangement; Logistics System; Space Optimization